Macroscopic thermal entanglement due to radiation pressure. - Ferreira, A; Guerreiro, A; Vedral, V (2006)
Can entanglement and the quantum behavior in physical systems survive at arbitrary high temperatures? In this Letter we show that this is the case for a electromagnetic field mode in an optical cavity with a movable mirror in a thermal state. We also identify two different dynamical regimes of generation of entanglement separated by a critical coupling strength.